Keyphrase Extraction Using TextRank for Indonesian Text - Muhammad, Fadel; Yusliani, Novi; Rachmatullah, Muhammad Naufal (Fakultas Ilmu Komputer Universitas Sriwijaya, 2024)
Keywords are commonly used as a form of summary from scientific publications. But in determining keywords, it requires expertise in the related field and a long amount of time because you have to read and understand the entire contents of scientific publications. Keyphrase Extraction can be a solution to get relevant keywords in a short time based on titles and abstracts from scientific publications. TextRank method is used to extract keywords. This research will perform keyword extraction using the TextRank method for Indonesian text. The evaluation results of this study showed an accuracy value of 95.53% and an f1-score of 59.32% with a threshold configuration of 80% and using all keyword candidates.